Investigation on reliability and validity of Life Cycle Cost (LCC) data inputs of building - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (IIUM Press, 2016)
In this paper, our aim is to propose a research design and methodology to investigate the current state and practice of LCC in the Malaysian construction industry, with specific reference to data inputs. The focus of the research is to assess the availability, accessibility, updated and reliability of the data as inputs into the process of estimating the total cost of building ownership. The research seeks to evaluate the data requirements of LCC analysis in generating reliable, accurate and credible LCC analysis which can therefore enlighten the clients, building owners and LCC estimators on the appropriateness, readiness, reliability and accurateness of existing databases and cost classification systems for conversion and in monitoring the outputs of LCC analysis. The anticipated outcome of the research is a proposed conceptual model which is considered the most appropriate methodology to procure reliable and credible data inputs of LCC. The model is purposely designed to rectify the problems of data constrained and the lack of appropriate data inputs in conjunction with the employment of LCC techniques in the Malaysian construction industry. The conceptual model can be shared with the LCC practitioners who could likely benefit from the output of the research, and simultaneously reinforce the practice of LCC in the investment decision making process of the clients and building owners to attain the best value for money. The present research has ascertained three objectives in purposely to attain the research aim: i. To study the principles of LCC and its implementation in the construction industry with specific reference to data inputs ii. To investigate the current development of LCC application in the Malaysian construction industry and the central issues of LCC practice iii. On the basis of (1) and (2), to develop a conceptual model which can facilitate the LCC practitioners in the Malaysian construction industry to procure reliable and credible data inputs in effort to generate an accurate LCC analysis. The outcomes of the assessment will be reported as a methodology of the research. The authors expect comments and feedbacks in effort to further improve the methodology. The paper is produced to support dissertation for Doctorate programme undertaken by the first author.